2005
DOI: 10.1097/01.nmd.0000188977.44657.1d
|View full text |Cite
|
Sign up to set email alerts
|

Postmigration Living Problems and Common Psychiatric Disorders in Iraqi Asylum Seekers in the Netherlands

Abstract: In a previous community-based, national study among Iraqi asylum seekers, a long asylum procedure was found to have a higher risk for common psychiatric disorders than adverse life events in Iraq. In the present article, the postmigration period is considered in more detail and evaluated in relationship with psychiatric disorders. Respondents were interviewed with fully structured, culturally validated, translated questionnaires. With the use of a Post- migration Living Problems questionnaire, worries about al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
217
1
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(243 citation statements)
references
References 13 publications
15
217
1
10
Order By: Relevance
“…In particular, we noted significant differences between groups based on gender, with females scoring higher on the distress scale than males, which is also consistent with other research (Miller et al, 2006;Porter & Haslam, 2005;Schweitzer, Melville, Steel, & Lacherez, 2006). Unemployment, not being able to speak English, being previously married (either divorced or widowed), and having only minimal education were also associated with an increased risk of psychological distress as reported elsewhere (Beiser & Hou, 2001;Laban, Gernaat, Komproe, van der Tweel, & De Jong, 2005;Nwadiora & McAdoo, 1996). Many of these variables are interrelated: learning English could be more difficult for people Can't be treated, struggle through alone with limited literacy skills and those with minimal education may have less English at the time of migration, which in turn will impact on employability.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In particular, we noted significant differences between groups based on gender, with females scoring higher on the distress scale than males, which is also consistent with other research (Miller et al, 2006;Porter & Haslam, 2005;Schweitzer, Melville, Steel, & Lacherez, 2006). Unemployment, not being able to speak English, being previously married (either divorced or widowed), and having only minimal education were also associated with an increased risk of psychological distress as reported elsewhere (Beiser & Hou, 2001;Laban, Gernaat, Komproe, van der Tweel, & De Jong, 2005;Nwadiora & McAdoo, 1996). Many of these variables are interrelated: learning English could be more difficult for people Can't be treated, struggle through alone with limited literacy skills and those with minimal education may have less English at the time of migration, which in turn will impact on employability.…”
Section: Discussionmentioning
confidence: 80%
“…For example, the high-profile stabbing of an Afghan former refugee taxi driver in Christchurch at the end of 2008 sent shockwaves through the small, close-knit community, highlighting concerns of vulnerability and prompting many to question their long-term settlement realities amid reports that he often felt intimidated by drunken and aggressive customers and faced constant abuse and threats of violence (Anon, 7 December 2008). Discrimination has been reported as a significant stressor in previous studies (Laban et al, 2005;Taloyan et al, 2006), and, apart from this incident which occurred after data collection, most of the negative comments concerning perceived discrimination and derogatory discourses were from Australian participants. In particular, some people mentioned that attitudes to Muslims had changed since 9/11, and they felt that this potentially affected their acceptance within the wider society, even after many years.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidity of PCBD and/or PTSD with other psychiatric disorders such as major depressive disorder (MDD) (Kessler, Sonnega, Bromet, Hughes, & Nelson, 1995; Schaal, Dusingizemungu, Jacob, Neuner, & Elbert, 2012), psychotic disorders (Sareen, Cox, Goodwin, & Asmundson, 2005) and substance abuse disorders (Kessler et al, 1995) is often observed. Furthermore, refugees are confronted with ongoing stressors that can fuel the risk for psychopathology (Laban 2004, 2005), such as insecurity about residential status, concerns about wellbeing of family members left behind, socioeconomic disadvantage, and adaptation to the host culture.…”
mentioning
confidence: 99%
“…Postmigration stressors, such as asylum regulation problems, uncertainty about the future, difficult living and social conditions as well as worries about family members in the home countries can interfere with the psychological recovery process and may foster the aggravation and chronification of mental health problems (Laban, Gernaat, Komproe, Van Der Tweel, & de Jong, 2005; Norris, Aroian, & Nickerson, 2011). Despite their overall high level of psychological impairment, refugees have limited access to appropriate medical and psychological care in many western countries, such as Germany, as structural barriers (i.e.…”
Section: Introductionmentioning
confidence: 99%